PERBANDINGAN INHIBISI α-MANGOSTIN, β-MANGOSTIN, DAN γ-MANGOSTIN TERHADAP PROTEIN AKT-KINASE PADA SEL KANKER PANKREAS SECARA MOLECULAR DOCKING - Harry Noviardi; Armi Wulanawati; Muhamad Sholehuddin Malik Ibrohim (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2016)
The mangosteen pericarp contains a class of compounds called xanthones, including α-mangostin, β-mangostin, and, γ-mangostin. Mangosteen products have become popular natural medicine. cancer is a malignant tumor types are particularly deadly caused by proliferative effects to inhibit apoptosis cell. Akt protein is considered to be the key downstream effector of reducing apoptosis. This study aims to determine the ratio of the potential of α-mangostin, β-mangostin, γ-mangostin as inhibitors of Akt protein of pancreatic cancer cells by the Gibbs free energy (ΔG), inhibition constants, hydrogen interactions. The computationally study using molecular docking method.Based on the analysis docking, γ-mangostin provides the potential for better inhibition than gemcitabine.